Molecular approaches for bacterial azoreductases - Montira Leelakriangsak (Songklanakarin Journal of Science and Technology (SJST), 2013)
Azo dyes are the dominant types of synthetic dyes, widely used in textiles, foods, leather, printing, tattooing, cosmetics, and pharmaceutical industries. Many microorganisms are able to decolorize azo dyes, and there is increasing interest in biological waste treatment methods. Bacterial azoreductases can cleave azo linkages (-N=N-) in azo dyes, forming aromatic amines. This review mainly focuses on employing molecular approaches, including gene manipulation and recombinant strains, to study bacterial azoreductases. The construction of the recombinant protein by cloning and the overexpression of azoreductase is described. The mechanisms and function of bacterial azoreductases can be studied by other molecular techniques discussed in this review, such as RT-PCR, southern blot analysis, western blot analysis, zymography, and muta-genesis in order to understand bacterial azoreductase properties, function and application. In addition, understanding the regulation of azoreductase gene expression will lead to the systematic use of gene manipulation in bacterial strains for new strategies in future waste remediation technologies.